Pengaruh Suhu Pengeringan Terhadap Kadar Air, Kadar Flavonoid dan Aktivitas Antioksidan Daun dan Umbi Rumput Teki (Cyperus rotundus L.) - Syafrida, Mulia; Darmanti, Sri; Izzati, Munifatul (Bioma : Berkala Ilmiah Biologi, 2018)
Purple nutsedge (Cyperus rotundus) is one of the medicinal plants that are potential to be developed as one source of antioxidants. This plant is quite interesting to developed because it is cheap and easy to obtain. The part of  purple nutsedge that often used is the tuber, leaves have not been widely used, whereas it contains flavonoids that can be used as an antioxidant. Post harvest handling is very important, especially in drying method. Drying aims to get a simplicia that is not easily damaged so it can be stored for a long time. This research was aimed to study differences of water content, flavonoids and antioxidant activity in leaves and tubers to the effect of different drying temperatures. The experimental analysis of this research is a Completely Randomized Design of two factors: the influence of different drying temperature (control (± 27 ºC), 30 ºC, 40 ºC and  50 ºC) and different parts of organs (leaves and tubers) with each of the three time repetition. Parameters include the study of  water content, levels of flavonoids and antioxidant activity. Data were analyzed using ANOVA followed by Duncan’s test at the level of 95%. The results showed that there was no interaction between drying temperature and organ difference in water content, flavonoids and antioxidant activity of purple nutsedge. Leaves of purple nutsdege have flavonoids and antioxidant activity is higher than the bulb. Water content, flavonoids and antioxidant activity decreases with increasing drying temperature.Keywords: purple nutsedge (Cyperus rotundus L.), drying temperature,  flavonoids, antioxidant activity